"It's people you know": the role social networks play in micro-informal markets - Massen, Alisha J. (Kansas State University, 2012)
Informal markets are prevalent all over the globe. The work done in such markets is often for the purposes of supplementary or subsistence income and it is done by men, women, and children. The purpose of my research was to understand how micro-informal markets are created by informal workers in Manhattan, Kansas. This was done through examining how informal workers used their social networks to find customers and how customers used their social networks to find informal goods and services produced by such workers, or more specifically, how micro-informal markets were created. This builds on the economic theory of embeddedness, which states social relations are an important part of the exchange process even in today's capitalistic market economy. In addition, my research also looked at why customers consumed from informal workers, why informal workers decided to go into business for themselves, how the city of Manhattan, Kansas viewed informal workers and whether city officials and affiliates encouraged informal businesses or not.
Keywords: Informal markets; Embeddedness; Market creation; Informal economy; Economics (0501); Sociology (0626)